PERBANDINGAN EFEKTIVITAS DOSIS EKSTRAK BIJI ALPUKAT YANG DIPROSES DENGAN MILLING TERHADAP PENURUNAN KADAR GULA DARAH PADA TIKUS - Clarence Marks Alief; Jojor Lamsihar Manalu (Atma Jaya Catholic University of Indonesia, 2020)
Introduction: Diabetes is a metabolic disease of which the pancreas is unable to produce insulin, a hormone that regulates blood sugar level or the body is unable to use insulin effectively. Diabetes causes several problems such as vision impairment, cardiovascular diseases, renal diseases and other illnesses. Diabetes is usually treated with anti-diabetic medication or with insulin. However, nowadays people are looking into alternative treatments which use natural ingredients. One such ingredient, among others is avocado seed (Persea Americana Mill.) extract. Avocado seeds is chosen for this research, as it has astringent and flavonoids which are proven to have anti-diabetic effect. Method: This is an experimental study using Sprague-Dawley strain rats. The rats were separated into 4groups, group as a negative control, and group II, III, and IV as experimental groups. The rats in the test group were injected with alloxan to induce diabetes, then the rats were given avocado seed extract of different concentration every day for five days. The avocado seed extract is obtained by first milling the seeds, so they become soft powder, and then extracting the seed using maceration. Results: Treatment with avocado seed extract caused a decrease in blood sugar level in group II, III, and IV.One Way Anova statistical test resulted in a value of p=0,046 therefore the decrease in blood sugar level wassignificant. However, Tukey HSD statistical test result showed that no test group is significantly different from one another. Conclusion: Treatment with avocado seed extract(dose of 150mg/kg, 300mg/kg, and 450mg/kg) caused adecrease in blood sugar that is statistically significant, however no dose of the avocado seed extract issignificantly more effective than the other